Impact of Seed Pre-Soaking in Saline and Salicylic Acid on Germination and Nutritional Quality of Radish Microgreens - Tarek Abd elkader; Tahany Aly; Yasser Elgabry; Usama Elbehairy (Arab Universities Journal of Agricultural Sciences)
This study was conducted to determine the impact of sodium chloride (2000 ppm) and salicylic acid (SA) concentrations (0, 50, 100, 150, and 200 ppm) on the nutritional value and germination of radish microgreens. The experiment was based on a completely random design with three replicates. Results indicated that applying SA at 50 and 100 ppm mitigates the negative effects of salinity, even better than higher concentrations, on the nutritional value and bioactive contents of radish microgreens where SA at 50 ppm lowered the sodium contents from 1.75 to 1.10 ppm in addition to increasing the moisture content. Applying SA at 50 and 100 ppm caused a noticeable increase in carbohydrates, proteins, fats, fibers and energy under unstressed condition. In addition, SA at 50 ppm caused a significant increase in oxalic and malic acid contents under both normal and salinity conditions while SA at 100 ppm significantly enhanced the levels of total phenols, flavonoids and antioxidants under salinity conditions. This practical study highlights the significant role of salicylic acid, at 50 and 100 ppm, in increasing the levels of phytochemicals and minerals, hence improving the nutritional value of microgreen radishes.